Education Sector When Applying Digital Technology - Hien, Do Thi; Phi, Pham Trinh Hong; Phương, Le Thi Nam (Universitas Komputer Indonesia, 2024)
Teaching and learning can be improved through digital technology by being more proactive in interacting with students, making students feel more interested and promoting a more engaging learning environment. It can be seen that IT applications provide students and teachers with new ways to communicate more easily and quickly. Multimedia education has made it easier to find and absorb knowledge, contributing to motivating students to improve their self-study ability. Furthermore, a dialogue can be opened based on digital technology between different countries and different cultures, from which purposeful intercultural communication is promoted. It also brings new learning opportunities for students and enriches the educational space. The application of digital technology helps schools more easily communicate information related to student learning to parents as well as optimize the learning process. The study is based on the analysis of relevant research documents to identify a number of factors that need to be considered in the process of digital transformation in education.